Some General New Einstein Walker Manifolds - Mehdi Nadjafikhah; Mehdi Jafari (Advances in Mathematical Physics, 2013)
Lie symmetry group method is applied to find the Lie point symmetry group of a system of partial differential equations that determines general form of four-dimensional Einstein Walker manifold. Also we will construct the optimal system of one-dimensional Lie subalgebras and investigate some of its group invariant solutions.